Evaluation of asymptomatic subjects with low forced expiratory ratios (FEV1/VC). Issue 6 (June 1994) - Kivity, S; Solomon, A; Schwarz, Y; Trajber, I; Topilsky, M
Abstract : BACKGROUND–Heightened bronchial hyperreactivity is frequently associated with airflow limitation, atopy, or cigarette smoking. The purpose of this study was to evaluate healthy subjects with significantly low values of forced expiratory volume in one second/vital capacity % (FEV1/VC%) by measuring their airway response to exercise and methacholine challenge, compared with a control group with normal spirometric values. METHODS–Eighty four healthy subjects with significantly low flow rates (group A, FEV1/VC% < 2 SD% predicted) were evaluated and compared with 37 subjects with normal flow rates (group B). Static lung volumes, spirometric tests, exercise, and methacholine challenges were performed. RESULTS–Lung volumes were normal for both groups. Mean FEV1/VC% was 69% for group A and 82% for the control group. Salbutamol improved baseline FEV1 in eight subjects in group A (mean 15%), while methacholine induced a drop in FEV1 in 12 subjects. The dose-response curve to methacholine reached a plateau in all the responders. None of the subjects in the control group improved their baseline FEV1/VC% to salbutamol, but three showed bronchial hyperreactivity similar to those in group A. CONCLUSIONS–Bronchial hyperreactivity does not occur more often in asymptomatic subjects with mildly low FEV1/VC% so these subjects do not require special investigations for airway disease.